Overcoming the challenges of English vocabulary learning for students with autism spectrum disorder (ASD) through the development of virtual reality technology - Fairus Suryani Munir; Pratiwi Samad (Universitas Muhammadiyah Enrekang, 2025)
The use of Virtual Reality for students with special needs, such as ASD, provides a fairer opportunity for them to develop in learning foreign language vocabulary, in this case English. The research method applied was Human-Centered Design, carried out through stages such as: Context of Use Analysis, User Needs Analysis, Solution Design, and Solution Evaluation. The results of the study, after conducting trials with ASD students, produced a product specification in the form of a VR-based English vocabulary learning application for ASD children, featuring basic vocabulary content, simple navigation, ASD-friendly design, and progress tracking support for teachers/therapists. Furthermore, the validation of the developed Virtual Reality technology, based on assessments from media experts, content experts, and therapists, was declared Highly Valid. This conclusion was drawn from the results of the validity questionnaires given to the experts, as well as from the vocabulary mastery of ASD students after learning English using the developed Virtual Reality technology—showing that they were able to pronounce and articulate the vocabulary correctly, as well as recall the English words of the observed objects. Keywords: Virtual Reality, Autism Spectrum Disorder Students, Vocabulary, English